17β-estradiol alters mRNA co-expression after murine muscle injury and mild hypobaria. Issue 16 (November 2019) - Moore, Scott Emory; Voss, Joachim G; St. Pierre Schneider, Barbara
Here, we assessed the effects of 17β-estradiol exposure on mRNA co-expression patterns of muscle tissue during recovery in a closed muscle crush injury and hypobaria exposure murine model. Eighteen ovariectomized placebo-treated and 18 ovariectomized 17β-estradiol-treated female mice underwent closed muscle crush injury and hypobaric simulated flight. The mice recovered for 32, 96, or 192 h, and then were euthanized. Their harvested injured lateral gastrocnemius muscles underwent microarray analysis. We used weighted gene co-expression network analysis to construct a co-expression network for the control mice, and then applied the same network to the estrogen-treated mice. We compared the relationships between co-expression in gene modules over time between the two experimental groups. Enriched functional cluster analyses of significant co-expression network modules document a variety of different pathways of interest. Some of the functional cluster enrichments within several of the significantly correlated modules are related to the formation and function of microtubules. Our findings demonstrate that following a closed muscle crush injury in a murine model, the presence of 17β-estradiol alters mRNA co-expression patterns over time. It appears that estrogen promotes the expression of mRNA related to microtubule activity within the cytoskeleton of myofibers and in movement of organelles and receptors. Further study is needed, but the enrichment of these microtubule-related pathways may be integral in the muscle tissue regeneration process, and thus suggests that the presence of estrogen may promote muscle recovery through the work of the microtubules. Impact statement: This study uses a murine model to address the clinical situation of transporting soldiers or civilians who have sustained skeletal muscle trauma by air. Our findings show that crush-injured muscle tissue of ovariectomized, 17β-estradiol-treated mice exposed to mild hypobaric hypoxia exhibited mRNA co-expression patterns among pathways associated with microtubule-dependent processes. Palmitoylation and other pathways necessary for movement of estrogen receptors to the cell membrane were also differentially enriched in the estrogen-treated mice. These first findings reframe the discussion regarding estrogen effects during muscle recovery from an inflammation-oriented inquiry to that of a structural, cytoskeletal inquiry and support additional research to understand the non-inflammation-related influences of estrogen during muscle recovery. Also, these results may suggest a role for estrogen or estrogen-like substances to treat muscle trauma.